Tribology Characteristics between Polymner Nanosheets and Human Skin - Nakano, Shunsuke; Zhang, Sheng; M. Danial, Ibrahim; Sunami, Yuta (2020)
The purpose of this study is to investigate the contact mechanism between nanosheets and human fingertip skin controlled to tens of nanometers in terms of friction coefficient under two different conditions, dry and immersed is. Nanosheets of various thicknesses with controlled film thickness were prepared, and the frictional force between the nanosheets and the fingertip was measured using a three component dynamometer. The contact area was observed with a prism and the contact area ratio was calculated. From the experimental results, comparing the friction coefficient and the contact area ratio of the polymer nanosheet, it was found that the contact area ratio increases as the friction coefficient decreases. In addition, a much higher coefficient of friction was observed during drying than when immersed in water, and the coefficient of friction increased slightly with increasing load during immersion. Therefore, the findings of this study could contribute to the study of nanosheet mate rials and other skin applications.